Kontribusi hubungan kemiskinan dan disabilitas netra: Studi kasus di Indonesia dengan menggunakan Data IFLS tahun 2014 - Fera Febriana Sritutur (Jurnal Kependudukan Indonesia, 2022)
Various studies have explored the relationship between visual impairment and poverty. This study aims to enrich understanding on the relationship between poverty and visual disability in the Indonesian context. This study uses data from Wave 5 of the Indonesian Family Life Survey (IFLS), focused on individuals aged 25 and above in 2014. The method used in this study consists of descriptive analysis and logistic regression. This study found that there is no relationship between poverty and visual impairment. The empirical result shows that people who experienced visual disability tend to have a lower probability of being poor in 2014 compared to people without visual disability. Poor persons also have lower probability to be visually disabled in 2014. This finding tends to be slightly different from previous research which showed the bidirectional relationship between poverty and visual disability. This difference might be due to the indicator of visual disability used in this study. Based on the IFLS data, people with visual disability come from a non-poor family so that they were able to perform medical check up, including eye health check. The results of this study indicate that a person with visual disability is capable of performing various activities, including productive activities. They are also able to work and create income. Thus, there is the possibility that they do not experience severe visual disability